(untitled) (Research, Society and Development, 2022)
Objective: Estimating the trend in birth weight and its relationship with determining factors in the state of Alagoas, Brazil. Methods: This is an ecological time series study whose sample was composed of live births in the State of Alagoas from 1998 to 2018. The source was the Information System on Live Births. Data regarding birth weight, maternal sociodemographic characteristics, and pregnancy-related characteristics were collected from the Department of Informatics of the Unified Health System Data. In the data analysis, the linear polynomial regression method was used and a significance level of 5% was adopted. Results: 1,199,161 live births were analyzed. 85,375 (7.1%) were low birth weight (LBW). The highest rate of BPN occurred in 2013 (7.6%). Live births of mothers aged ≥35 years showed an increasing and significant trend of BPN with an annual mean increase of 13.4% of births with LBW (p<0.001). Mothers who had been studied for (8) years or more showed an increasing trend for children with LBW in the evaluated period (p<0.001). Gestational age between 22 and 36 weeks showed an increasing and significant trend of LBW (p=0.002). Conclusion: It was observed that the evolution of birth weight tends towards an overall stabilization of the prevalence of LBW. However, even in this context, it is essential to assess the dimension of birth weight and the factors associated with it to promote the program planning and public health policies.